THE ROLE OF LOCAL WISDOM IN ENVIRONMENTAL CONSERVATION AND TOURISM MANAGEMENT IN NAMU VILLAGE - Dewi, Ketut Ratna (International Journal of Cultural and Social Science, 2025)
This study analyzes the role of local wisdom in environmental conservation and the management of Namu Tourism Village in South Konawe Regency, Southeast Sulawesi. Using a descriptive qualitative approach through observation, in-depth interviews, and documentation, the research explores how customary values guide ecological practices. The findings show that prohibitions on illegal logging, collective water management, mutual cooperation (mosiho kampo), and nature-honoring rituals (moduo wonua) function as effective community-based mechanisms for preserving environmental balance. In tourism management, the application of Community-Based Tourism (CBT) encourages active community participation in regulating tourist activities and maintaining ecological sustainability. However, challenges arise from generational shifts in values, limited documentation of customary norms, and risks of cultural commercialization. Despite these constraints, opportunities exist through local government support and digital cultural promotion. The study concludes that integrating local wisdom, community participation, and adaptive cultural practices is essential for sustainable tourism development in Namu Village.